2001
DOI: 10.1046/j.1444-2906.2001.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the dolphin fish Corphaena hippurus on the east coast of Taiwan

Abstract: The dolphin fish, Corphaena hippurus Linnaeus, is one of the most important migratory fishes on the east coast of Taiwan. Present results are based on an investigation of 1439 specimens caught using long‐line and driftnet, and set net collected monthly between September 1996 and September 1997. The sex ratio of female to male and female combined was 65%, demonstrating a female predominance. Oocytes became mature and transparent when they attained 1.0 mm in diameter. The total number of oocytes per ovary was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 18 publications
8
32
1
2
Order By: Relevance
“…Nevertheless, according to Vazzoler (1996) and Wu et al (2001), this ratio might differ from 1:1 due to different growth rates, mortality rates and longevity for each sex, sexual inversion and migration to spawning grounds.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to Vazzoler (1996) and Wu et al (2001), this ratio might differ from 1:1 due to different growth rates, mortality rates and longevity for each sex, sexual inversion and migration to spawning grounds.…”
Section: Discussionmentioning
confidence: 99%
“…orientale differs from the majority of teleosts by the larger size of the male. These differences in sexual ratio have been explained by different hypothesis, such as physiological differences between sexes, mechanisms that makes males more inclined to be captured or less inclined to natural mortality (Boussou et al, 2010), growth rates (Kume & Joseph, 1966) and longevity (Wu, Su, & Kawasaki, 2001). Usually, a larger body volume would allow the female to allocate more eggs and therefore might be considered an evolutionary advantage (Moraes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Potoschi et al (1999), working with individuals from the Mediterranean Sea, found the highest values of GSI between June and September, when all the individuals sampled were mature, with a peak in July. Wu et al (2001) found peaks of GSI for males and females in February and March in Taiwan, but suggested that the dolphinfish has a long breeding season, during which it spawns almost continuously. Similarly, Alejo-Plata et al (2011) observed a long spawning season for the dolphinfish off Mexico, with several peaks of GSI and the top two happening in September-November and between February and April.…”
Section: Actively Spawningmentioning
confidence: 99%